Structure and mechanical behaviors of protective armored pangolin scales and effects of hydration and orientation. (March 2016) - Liu, Z.Q.; Jiao, D.; Weng, Z.Y.; Zhang, Z.F.
Abstract: As natural flexible dermal armor, pangolin scales provide effective protection against predatory threats and possess other notable properties such as anti-adhesion and wear-resistance. In this study, the structure, mechanical properties, deformation and damage behaviors of pangolin scales were systematically investigated with the effects of hydration and orientation evaluated. The scales are divided into three macro-layers constituted by overlapping keratin tiles with distinct lamellar arrangements which are further composed of lower-ordered lamellae. Both hardness and strength are significantly decreased by hydration; while the plasticity is markedly improved concomitantly, and as such, the mechanical damages are mitigated. The tensile strength invariably approximates to one third of hardness in value. The tensile deformation is dominated by lamellae stretching and pulling out under wet condition, which is distinct from the trans-lamellar fracture in dry samples. The compressive behaviors are featured by pronounced plasticity in both dry and wet scales; and notable strain-hardening capacity is introduced by hydration, especially along the thickness direction wherein kinking occurs. Inter-lamellar cracking is effectively alleviated in wet samples compared with the dry ones and both of them deform by macroscopic buckling. This study may help stimulate possible inspiration for the design of high-performance synthetic armor materials by mimicking pangolin scales. Highlights: Structure and mechanical behaviors of armored pangolin scales were clarified. The scale has hierarchical structure with three distinct layers of keratin tiles. Plasticity is markedly improved by hydration at a cost of hardness and strength. Fracture modes and mechanisms depend on orientation and hydration state. Compressive behavior is featured by notable plasticity and macroscopic buckling.